2D and 3D numerical simulations of dam-break flow problem with RANS, DES, and LES. (15th May 2023) - Simsek, Oguz; Islek, Huseyin
Abstract: In this study, dam-break flows occurring on different downstream/upstream water depth ratios (α = 0, 0.1, and 0.4) and different obstacle shapes are numerically modeled in 2D and 3D. The Finite Volume Method (FVM) is used in the numerical solution of the basic equations governing the propagation wave formed as a result of the dam-break, and the interface of water with air is calculated by the Volume of Fluid (VOF) method. In modeling turbulence stresses, four turbulence models particularly successful in curvilinear trajectories and high strain flows, namely the Re-normalization Group (RNG), Shear Stress Model (SST), Detached Eddy Simulation (DES), are employed for the 2D simulation, and Large Eddy Simulation (LES) for the 3D simulation. The numerical results are compared against the previous experimental results and the performance of the turbulence models is evaluated according to the Mean Absolute Relative Error (MARE) criteria. For the 2D analysis, it has been determined that the DES is more successful for α = 0, 0.1, and 0.4, whereas the SST is more successful for triangular and trapezoidal obstacles in the downstream region than other turbulence models. Comparing the 2D and 3D results, the 3D LES model is expected to be more compatible with the experimental water surface profiles for all conditions among the models used in the study. It has been concluded that turbulence models, in which the strain tensor is considered, are successful in modeling the propagation wave formed as a result of a dam-break. Highlights: Numerically obtained water surface profiles of dam-break flows under different conditions are compared against experimental results in terms of MARE. The success of RNG, SST, DES and LES models are investigated. SST and DES models are found to predict better flow with and without obstacles, respectively. 3D model (LES) predicts better than the 2D model (RNG, SST, DES).